Causes of resistance to PARP inhibitors and ways to overcome it. Case report of aggressive BRCA-related breast cancer - A. I. Stukan; A. Yu. Goryainova; S. V. Sharov; O. A. Goncharova; Z. K. Khachmamuk; V. V. Durov (Опухоли женской репродуктивной системы, 2022)
PARP inhibitors. However, in clinical practice, despite the proven antitumor efficacy of drugs, acquired resistance to PARP inhibitors leads to difficulties in selecting further therapy due unknown resistance mechanisms and absence of algorithm of action. Despite the various mechanisms of resistance to PARP inhibitors, the choice of subsequent combination therapy after the detection of resistance to PARP inhibitors should be based on an understanding of these mechanisms and the existence of heterogeneous metastatic process. At the same time, it is very important to study the molecular and genetic characteristics of the disease at each stage of progression, which will help to identify the cause of resistance and select the optimal treatment strategy. It seems that liquid biopsy of circulating tumor DNA, detection of circulating tumor cells, circulating microRNA or exosomes may be more suitable methods of molecular diagnostics than repeated biopsies. Currently, there are data on the identification of two types of resistance to PARP inhibitors: mechanisms independent and dependent on the BRCA1/2 gene and homologous DNA recombination repair (HRR) mechanisms. Strategies for using combinations of different therapeutic regimens in conjunction with PARP inhibitors are very promising options for preventing treatment resistance in view of the increasing number of patients with similar clinical course of the disease.In the presented clinical case, BRCA1-associated triple-negative breast cancer demonstrates an aggressive clinical course in case of adjuvant chemotherapy absence. Using the example of a clinical case, the effectiveness of therapy with the PARP inhibitor olaparib in disseminated BRCA1-mutated breast cancer, including those with brain metastases, was confirmed. At the same time, against the background of good tolerance and сlinical efficacy especially in the case of brain metastases, the use of the PARP inhibitor olaparib is a worthy alternative to chemotherapeutic regimens. The selection of subsequent therapy after a PARP inhibitor requires a balanced approach, taking into account the possible causes of crossresistance with chemotherapy regimens.